Emerging issues and barriers in access to menstrual hygiene management in a tribal district of India - Kakwani, Jyoti; Meena, Jitendra Kumar; Verma, Anjana; Dahiya, Neha (International Journal Of Community Medicine And Public Health, 2021)
Background: Access to Menstrual Hygiene Management (MHM) remains a critical challenge to Indian women especially in remote areas. The problem of poor availability, acceptance, and affordability of MHM products is further aggravated by negative social construct and environmental concerns. Poor menstrual hygiene is linked to significant morbidity and mortality due to reproductive tract infections (RTIs) and cervical cancer etc. Methods: A campaign “Chuppi Todo” was organized in Udaipur; a tribal district in Rajasthan aiming for menstrual health education of adolescent girls and mothers across public schools through interactive means. During the campaign interviews were conducted by trained field staff with participating girls to elicit perspectives related to menstrual hygiene and feedback of the education sessions. Results: Based on qualitative assesments it was observed that women largely ignore menstrual hygiene or follow old traditional practices. They don’t prefer using modern MHM products like sanitary pads etc owing to the difficulty in their disposal and embarrassment. Conclusions: The present study highlights existing knowledge gaps and barriers in providing universal access to MHM to adolescent girls and women living in remote areas in India.